2005
DOI: 10.1038/nature03344
|View full text |Cite
|
Sign up to set email alerts
|

Addition of human melanopsin renders mammalian cells photoresponsive

Abstract: A small number of mammalian retinal ganglion cells act as photoreceptors for regulating certain non-image forming photoresponses. These intrinsically photosensitive retinal ganglion cells express the putative photopigment melanopsin. Ablation of the melanopsin gene renders these cells insensitive to light; however, the precise role of melanopsin in supporting cellular photosensitivity is unconfirmed. Here we show that heterologous expression of human melanopsin in a mouse paraneuronal cell line (Neuro-2a) is s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

19
340
0
8

Year Published

2005
2005
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 357 publications
(367 citation statements)
references
References 29 publications
19
340
0
8
Order By: Relevance
“…In Neuro-2a culture, cells transfected with a human melanopsin cDNA, 11-cis-and 9-cis-retinal were both able to serve as chromophore (15). Interestingly, in these cells, all-trans-retinal could function as chromophore if cells were pretreated with longwavelength light (15).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In Neuro-2a culture, cells transfected with a human melanopsin cDNA, 11-cis-and 9-cis-retinal were both able to serve as chromophore (15). Interestingly, in these cells, all-trans-retinal could function as chromophore if cells were pretreated with longwavelength light (15).…”
Section: Discussionmentioning
confidence: 99%
“…Mice with outer retinal dysfunction or degeneration that also lack melanopsin show no nonvisual photoreceptive function (9, 10); no light responses of ipRGCs can be recorded from opn4 Ϫ/Ϫ animals (9, 11, 12); and heterologously expressed melanopsin confers photosensitivity to nonphotoreceptive cells including Xenopus oocytes and immortalized mammalian cell lines (13)(14)(15)(16). Although the requirement for exogenous retinal differs in different heterologous expression systems (e.g., HEK293-TrpC3 cells do not require exogenous retinal; ref.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Under broadband natural or artificial light exposure, these two states exist in equilibrium. However, under monochromatic light exposure, it was shown that whereas especially short wavelengths initiated the phototransduction cascade (from R to M), long wavelengths could restore responsiveness by regeneration of the M to the R states (Melyan et al, 2005;Mure et al, 2009). The light intensities used in Mure et al's study to drive the M state back to the R state were quite high.…”
Section: Effects Of Artificial Dawn On Sleep Inertia 1233mentioning
confidence: 99%
“…In contrast to perturbations achieved by the use of reagents or temperature change, photoperturbation provides an ideal range of adjustability in timing and strength. Although most mammalian cells cannot sense light, recent studies have shown that mammalian cells (Neuro-2a; HEK293) become photoresponsive following the introduction of an exogenous G-protein-coupled photoreceptor, melanopsin (Melyan et al 2005;Qiu et al 2005). It was reported that photostimulation of melanopsin triggers a release of intracellular calcium mediated through the G q -protein signaling pathway, and, importantly, there are several reports that mammalian cellular clocks can be reset by the G q -protein signaling pathway involving a release of intracellular calcium (Balsalobre et al 2000a;Tsuchiya et al 2005).…”
Section: Control Of Clocksmentioning
confidence: 99%